ANALYSIS OF GRAMMATICAL ERROR IN WRITING EXPOSITORY ESSAY MADE BY THIRD YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research was aimed to analyze the grammatical error made by third year students of English Study Program based on Dulay’s Surface Strategy Taxonomy Theory (1982). The research was conducted at English Study Program of Universitas Riau. In conducting the research, the researcher distributed instrument of writing test to class C of third-year students of English Study Program of Universitas Riau. 37 students employed in this study were given the instrument of writing test. The research design was descriptive research that focused on quantitative approach. The data were collected by using Google Classroom. The collected data were nalyzed by three raters and the result were calculated by using Microsoft Excel. The findings of this study revealed that the students made 473 errors with the highest error was Double Marking (21% of total error) and the lowest error was regularization in Addition (7% of total error). Furthermore, in order to be good in using grammar especially in writing, several recommendations were given to the students such as the students need to do more excercie to understand about grammar as well as to practice more in productive skills in order to implement grammar learnt as well as receptive skills in order to understand how grammar is used.Key Words: Error Analysis, Grammatical Error, Writing.